Advanced practice nursing leadership : a global perspective - Accad, Aila (Advanced practice in nursing / series editor Christophe Debout, 2020)
This book is distinctive in its focus on Advanced Practice Nursing leadership globally. It has a unique structure, first highlighting global APN leadership and then including case studies on leadership from various regions around the world. This beneficial and practical book has a specific emphasis on academic, clinical and policy leadership and is relevant for all readers. Finally, a section on leadership development focuses on coaching and mentoring, business acumen, collaboration and patient advocacy provides an important contribution.